2010
DOI: 10.1007/s11104-010-0571-3
|View full text |Cite
|
Sign up to set email alerts
|

Traits related to differences in function among three arbuscular mycorrhizal fungi

Abstract: Diversity in phosphorus (P) acquisition strategies was assessed among three species of arbuscular mycorrhizal fungi (AMF) isolated from a single field in Switzerland. Medicago truncatula was used as a test plant. It was grown in a compartmented system with root and root-free zones separated by a fine mesh. Dual radioisotope labeling ( 32 P and 33 P) was employed in the root-free zone as follows: 33 P labeling determined hyphal P uptake from different distances from roots over the entire growth period, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
86
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(106 citation statements)
references
References 42 publications
(63 reference statements)
7
86
0
3
Order By: Relevance
“…In a similar study on Araucaria angustifolia, Moreira et al (2006) showed similar rates of root colonization in spring. A reasonable colonization rate is usually about 40% (Thonar et al 2011). In the present study, based on observation of vesicle, arbuscule and mycelia in roots, AMF colonization rates were more than 51% and 32% of roots in spring and autumn, respectively.…”
Section: Discussionsupporting
confidence: 46%
“…In a similar study on Araucaria angustifolia, Moreira et al (2006) showed similar rates of root colonization in spring. A reasonable colonization rate is usually about 40% (Thonar et al 2011). In the present study, based on observation of vesicle, arbuscule and mycelia in roots, AMF colonization rates were more than 51% and 32% of roots in spring and autumn, respectively.…”
Section: Discussionsupporting
confidence: 46%
“…papyrifera and B. pilosa seedlings that received an AM fungal treatment showed positive feedback in terms of biomass and nitrogen and phosphorous acquisition (Figure 1(a), 1(b), 1(c)), which was consistent with the results reported in many related studies showing that AM fungi change the growth and nutrient uptake of their host plants (Gustafson & Casper 2006;Hart et al 2013;Jansa et al 2008;Kiers et al 2011;Thonar et al 2011). Differences in the influence of an AM fungal association on the performance of plant traits for biomass and nitrogen and phosphorus acquisition depending on the plant species and the AM fungal composition have previously been explained as a method of avoiding competition between individuals (Jansa et al 2008;Kiers et al 2011).…”
Section: Effects Of Fungi Fungal Composition and Species On Plant Grsupporting
confidence: 90%
“…Differences in the influence of an AM fungal association on the performance of plant traits for biomass and nitrogen and phosphorus acquisition depending on the plant species and the AM fungal composition have previously been explained as a method of avoiding competition between individuals (Jansa et al 2008;Kiers et al 2011). Previous studies have shown that inoculating plants with multiple AM fungi was beneficial for the nutritional uptake of the host plant (Gustafson & Casper 2006;Thonar et al 2011), which was consistent with our results for the B. papyrifera seedlings that received the MI treatment (Figure 1(b), 1(c)). However, Edathil et al (1996) and Hart et al (2013) argued that inoculating plants with a single AM fungus can derive the biggest benefit.…”
Section: Effects Of Fungi Fungal Composition and Species On Plant Grmentioning
confidence: 99%
“…Hence, the most traditional agricultural practices were unfavorable to enhance the AMF benefits in citrus orchards. In the present study, the higher AMF diversity in SC might be advantageous in improving various orchard ecology functions as different AMF species were highly variable in several functional traits (Thonar et al 2011).…”
Section: Results and Disscussionmentioning
confidence: 72%